A Closed Literature-Based Discovery Technique Finds a Mechanistic Link Between Hypogonadism and Diminished Sleep Quality in Aging Men - Miller, Christopher M. (Associated Professional Sleep Societies, LLC, 2012)
STUDY OBJECTIVES: Sleep quality commonly diminishes with age, and, further, aging men often exhibit a wider range of sleep pathologies than women. We used a freely available, web-based discovery technique (Semantic MEDLINE) supported by semantic relationships to automatically extract information from MEDLINE titles and abstracts. DESIGN: We assumed that testosterone is associated with sleep (the A-C relationship in the paradigm) and looked for a mechanism to explain this association (B explanatory link) as a potential or partial mechanism underpinning the etiology of eroded sleep quality in aging men. MEASUREMENTS AND RESULTS: Review of full-text papers in critical nodes discovered in this manner resulted in the proposal that testosterone enhances sleep by inhibiting cortisol. Using this discovery method, we posit, and could confirm as a novel hypothesis, cortisol as part of a mechanistic link elucidating the observed correlation between decreased testosterone in aging men and diminished sleep quality. CONCLUSIONS: This approach is publically available and useful not only in this manner but also to generate from the literature alternative explanatory models for observed experimental results. CITATION: Miller CM; Rindflesch TC; Fiszman M; Hristovski D; Shin D; Rosemblat G; Zhang H; Strohl KP. A closed literature-based discovery technique finds a mechanistic link between hypogonadism and diminished sleep quality in aging men. SLEEP 2012;35(2):279-285.